Linking household wealth and resource use : a case study in the Agincourt rural district of South Africa - Ndengejeho, Henry Michael (My University, 2008)
The importance and value of natural resources to rural livelihoods have been well documented. However, most studies quantify mean consumption and direct use values across households, overlooking the significant differences that occur within and between households. This study investigated the influence of household wealth on the use of natural resources and the direct use values derived from them in the Agincourt subdistrict of the Bushbuckridge local municipality in Mpumalanga Province, rural South Africa. Four natural resources were examined, namely edible herbs, wild fruits, edible insects, and fuelwood, although 13 additional resources were referred to. Households were grouped into three socio-economic classes (poor, medium and wealthy) based on assets possessed by the household, to explore wealth-related differences and similarities in the use and value of natural resources. The asset register included household possession of assets such as vehicles, appliances, cellphones, wheelbarrows, as well as the number and type of dwellings in the homestead yard. The households’ use of natural resources was compared among the different socio-economic classes. The study found no difference in the number of natural resources used by households of different socioeconomic status. The type of resources used was influenced by household’s possession of material resources. Poor households relied more on natural resources than wealthier households for their daily food and energy needs. The household consumption and direct use values of edible herbs and fuelwood were higher in poor households. The per capita consumption and direct use values of edible herbs, edible insects and fuelwood were higher in poor households too, although only fuelwood differed significantly among socio-economic classes. This study highlighted that wealth in isolation may not have an obvious influence on natural resources use, and that culture and gender play significant roles too. The assessment of household wealth is not easy and should be based on multiple criteria (i.e. a proper livelihoods analysis) to fully capture all relevant aspects of wealth.